Most Common reasons for ICU admissions during pregnancy in Asian mothers - Iman Hashemi Petroudi; Sepideh Fanaei; Babak Dabbaghi; Farzaneh Fazeli; Sonia Nourkhomami; Alireza Sedaghat (Mashhad University of Medical Sciences, 2020)
Introduction: Maternal mortality during childbirth is a well-known indicator of the quality of maternity services that reflects the level of development of a country. Moreover, it is associated with various social, economic and cultural levels of a country. Admissions to the Intensive Care Unit (ICU) may be considered an objective indicator of severe maternal diseases. One of the most important health indicators is to reduce maternal mortality and the significance of examining the reasons for its occurrence. Therefore, this systematic review aimed to investigate the reasons why pregnant women are admitted to the ICUs. Methods: The search process was conducted through the Google Scholar, PubMed, Magiran, Science Direct and SID databases. The search was originally conducted in January 2018 and updated in February 2018. The keywords searched were ICU and Intensive Care Unit, which in combination with Pregnancy, Pregnant Women and Obstetric Patients searched the published studies from the beginning until 2018. Results: According to the findings, hemorrhage and preeclampsia are the most common causes of hospitalization of pregnant women in the ICUs. Based on the findings of this study, hemorrhage with an incidence rate of 7 to 62% was the most common admission causes of pregnant women to the ICUs in Asian countries. The second reason for pregnant women referral to the ICUs was preeclampsia and eclampsia (2 to 25%). Other common causes for the ICU admissions during pregnancy included sepsis, HELLP syndrome, peripartum cardiomyopathy, cerebral palsy syndrome, and acute fatty liver of pregnancy. Conclusion: Bleeding and preeclampsia, sepsis, HELLP syndrome, peripartum cardiomyopathy, embolism of cerebral palsy and acute fatty liver of pregnancy are the most common causes of hospitalized pregnant women.